Raman spectra of sol-gel auto-combustion synthesized Mg-Ag-Mn and Ba-Nd-Cd-In ferrite based nanomaterials. Issue 1 (January 2020) - Jasrotia, Rohit; Singh, Virender Pratap; Kumar, Rajesh; Singh, Mahavir
Abstract: In this present work, we have done the comparison of raman spectra of hard ferrite i.e. Ba0.7 Nd0.3 Cd0.5x In0.5x Fe12-x O19 (x = 0.0, 0.2, 0.3) and soft ferrite i.e. Mg1-x Mnx Agy Fe2-y O4 (x = 0.1, 0.2, 0.3, 0.4, 0.5, y = 0.0, 0.1, 0.2, 0.3, 0.4) which defines the novality and achievement of this work. These ferrite based nanomaterials were synthesized with the aid of sol-gel auto-combustion method in order to analyze Raman spectra carried with 514.5 nm laser of argon ion (50 mW) by using Renishaw inVia Reflex micro-Raman spectrometer. The Raman spectra of synthesized Mg1-x Mnx Agy Fe2-y O4 (x = 0.1, 0.2, 0.3, 0.4, 0.5, y = 0.0, 0.1, 0.2, 0.3, 0.4) and Ba0.7 Nd0.3 Cd0.5x In0.5x Fe12-x O19 (x = 0.0, 0.2, 0.3) ferrites confirmed the formation of five active Raman vibrational modes (A1g  + Eg +3T2g ). Out of this, Raman spectral analysis of Mg1-x Mnx Agy Fe2-y O4 (x = 0.1, 0.2, 0.3, 0.4, 0.5, y = 0.0, 0.1, 0.2, 0.3, 0.4) nanomaterials confined that Eg mode is found in the range of 194.74–212.77 cm −1, T2g vibrational mode is found to be in the range of 326.17–339.58 cm −1, 482.27–587 cm −1 and 608.84–614.02 cm −1 whereas A1g configuration mode is found to be in the range of 685.47–701.52 cm −1 . In addition to this, Raman spectral analysis of Ba0.7 NdO.3 Cd0.5x In0.5x Fe12-x O19 (x = 0.0, 0.2, 0.3) nanohexaferrites consists of five Raman active vibrational modes in the range as ν1  = 329.02–334.70 cm −1, ν2  = 410.33–410.90 cm −1, ν3  = 522.06–524.65 cm −1, ν4  = 612.52–616.66 cm −1 and ν 5  = 679.97–685.16 cm −1 . The Raman spectra of both the compositions continuously indicates the symmetric and anti-symmetric behaviour of the band position of spinel and hexagonal magnetic nanomaterials.